RESPONSIBILITY OF INFLUENCERS WHO CONDUCT STOCK POMMS AS A LAW ENFORCEMENT MEASURE FOR INVESTORS - Agatha Edelweiss; Joanne Emmanuel; Ricky Siregar (Jurnal Ilmiah Advokasi, 2024)
Many stock investment influencers often engage in stock pumping and dumping on social media. "Pompom" is a term for "pump and dump" which involves individuals or groups. Those involved in stock pumping and dumping frequently share information about stocks they already own or plan to buy. This indirectly shapes opinions and captures the attention of their followers to buy stocks as per their desires, often enhanced by enticing details. This attracts people to invest in the recommended stocks. Pompom influencers target millennial and novice stock investors, as these groups seek quick and substantial profits. When millennial and novice investors begin purchasing stocks, they often expect only gains without considering potential losses. Due to their limited knowledge, beginners often rely solely on the provocations from stock-pumping influencers on social media to make decisions about which stocks to buy. They may skip technical and fundamental analysis of the companies behind the stocks they purchase. This means they don't investigate whether these pompom influencers have conducted thorough assessments of the recommended stocks through social media. Those involved in stock pumping can be held accountable under securities laws and criminal codes.Keywords: stock investment law, stock influencers, pump and dump